Sodium alginate microspheres for extending drug release: formulation and in vitro evaluation - M L Soni; M Kumar; K P Namdeo (International Journal of Drug Delivery, 2010)
In the present study, spherical microspheres of theophylline (TP) using sodium alginate as the hydrophilic carrier were prepared to prolong the release. The shape, surface and size characteristics were determined by scanning electron microscopy. The microspheres were found to be discreet and spherical in shape and had a smoother surface. The mean diameter of seven alginate microspheres formulations were between 7.6 ± 0.52 and 22.35 ±0.31 μm. It was observed that mean particle size of the microspheres increased with an increase in the concentration of polymer. The entrapment efficiency was found to be in the range of 70–93%. Optimized alginate microspheres were found to possess good sphericity, size and adequate entrapment efficiency. The in vitro release studies were carried out in pH progression media (pH 1.2, 2.5, 4.5, 7 and 7.4 solutions). Results indicated that percent drug release decreased with an increased alginate concentration. TP-loaded Alginate microspheres showed extended in vitro drug release thus use of microspheres potentially offers sustained release profile along with improved delivery